Endovascular and Hybrid Open and Endovascular Management of Blunt and Penetrating Zone III Carotid Artery Injuries - Strauss, Shira A; Power, Adam; Nagpal, Sudhir K; Tso, Michael K; Brenner, Megan L; DuBose, Joseph J; Roberts, Derek J (Journal of Endovascular Resuscitation and Trauma Management, 2022)
Injuries to zone III of the carotid artery, located between the angle of the mandible and the skull base, are uncommon, associated with a high risk of adverse neurologic events and mortality, and challenging to treat. These lesions are difficult to access and treat surgically due to their anatomic location. Therefore, endovascular and hybrid open and endovascular techniques have emerged as a minimally invasive, and in many cases, safer and more effective alternative to open surgery. Endovascular techniques for use in this anatomical region include balloon catheter tamponade, embolization, balloon angioplasty, and endovascular stenting. Selection of the most appropriate treatment strategy is dependent on the: 1) concomitant injuries of the patient, 2) location (external versus internal carotid artery) and nature (intimal tear, dissection, pseudoaneurysm, transection, occlusion, or arteriovenous fistula) of the injury, and 3) whether the operating surgeon believes it is necessary to revascularize or sacrifice the injured carotid artery. The purpose of this article is to review the present endovascular and hybrid open and endovascular therapies available for zone III penetrating and blunt carotid trauma. We begin by describing the clinical presentation and diagnosis of these injuries and then discuss management of an undifferentiated zone III vascular injury. This is followed by a discussion of the management of zone III external and then internal carotid artery injuries. We conclude by describing postoperative management, follow up, and future directions.